Customer knowledge sharing in cross-border mergers and acquisitions: The role of customer motivation and promise management - Degbey William Y.; Pelto Elina (Elsevier, 2025)
Knowledge is a vital source of competitive advantage and renewal for contemporary organizations. However, to date, few studies have scrutinized how mergers and acquisitions (M&As)—processes dependent on knowledge sharing—offer a valuable inter-organizational context through which to understand the attainment of customer knowledge sharing following M&As. Applying an integrated theoretical perspective from customer relationship management and M&A performance research, we study a Chinese–Finnish acquisition and customer firms of the acquired party across four advanced Western countries. We find that customer knowledge sharing is an active relationship management process that relies on the factors of customer dedication-based motivation vs. customer concerns about M&As to maintain relationships after acquisitions. In addition, and more importantly, we find that the promise management mechanisms—making promises, enabling promises, and keeping promises—of the M&A parties reinforce the motivational factors to maintain customer knowledge sharing in cross-border M&As. We propose a conceptual framework of customer knowledge sharing in cross-border M&As.